2012
DOI: 10.1039/c2nr31629c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and high-pressure transformation of metastable wurtzite-structured CuGaS2 nanocrystals

Abstract: The metastable wurtzite nanocrystals of CuGaS(2) have been synthesized through a facile and effective one-pot solvothermal approach. Through the Rietveld refinement on experimental X-ray diffraction patterns, we have unambiguously determined the structural parameters and the disordered nature of this wurtzite phase. The metastability of wurtzite structure with respect to the stable chalcopyrite structure was testified by a precise theoretical total energy calculation. Subsequent high-pressure experiments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 45 publications
(45 reference statements)
1
42
0
Order By: Relevance
“…In fact, the common formula Cu I B III C VI 2 is only valid for stoichiometric compounds where the Cu:Ga ratio is 1:1. 26,29 To synthesize the gallium-rich wurtzite Cu−Ga−S ternary nanocrystals, Cu:Ga ratios targeting 1:3 and 1:5 gave an average Cu:Ga composition of 1:2.1 and 1:4.1, respectively. The gallium-rich ternary Cu-Ga-S with the formula CuGa 2.1 S 3.7 and CuGa 4.1 S 6.7 were obtained (these actual formula are used hereafter).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the common formula Cu I B III C VI 2 is only valid for stoichiometric compounds where the Cu:Ga ratio is 1:1. 26,29 To synthesize the gallium-rich wurtzite Cu−Ga−S ternary nanocrystals, Cu:Ga ratios targeting 1:3 and 1:5 gave an average Cu:Ga composition of 1:2.1 and 1:4.1, respectively. The gallium-rich ternary Cu-Ga-S with the formula CuGa 2.1 S 3.7 and CuGa 4.1 S 6.7 were obtained (these actual formula are used hereafter).…”
Section: Resultsmentioning
confidence: 99%
“…Many CdS-based photocatalysts have been employed and thoroughly investigated since the 1980s, [7][8][9][10][11][12][13][14][15][16][17] and the ternary and the quaternary metal sulfides have been recently investigated, providing additional variety in selection of elements and resultant tunable bandgaps. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] The synthesis of ternary copper gallium sulfide-based nanocrystals has attracted much attention in recent years because they are more environmentally benign than their Cd-or Pb-based counterparts. 21 Moreover, they have a promising potential for many applications such as photovoltaic, lightemitting devices, radiation detection, and photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CuGaS 2 nanocrystals exhibit excellent activity in solar water splitting [42,43], biological and chemical sensing [44,45]. Ascribing to its wide band gap energy (2.2-2.5 eV) [46,47] corresponding to the green light region and direct transition [29,[48][49][50][51], CuGaS 2 nanocrystals could be an optimum candidate for the QDSSCs. However, very few studies on CuGaS 2 QDSSCs were reported.…”
Section: Introductionmentioning
confidence: 99%